Tari Sufi sebagai Media untuk Meningkatkan Kecerdasan Spiritual Remaja : (Study Komunitas Dervishe Pekalongan) - Bimantoro, Bayu; Jamaluddin Miri, Seyed (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Sufi dance is not just an ordinary dance; it also has spiritual value because it is a medium for expressing devotional remembrance, remembering, and contemplating God. Therefore, of course, Sufi dance is closely related to spiritual intelligence. Spiritual intelligence is an individual’s ability to listen to his conscience or the whisper of divine truth in how he makes choices, empathizes and adapts, leading him to ma’rifatullah. This research aims to find out about increasing the spiritual intelligence of teenagers who are members of the Dervishe Pekalongan Sufi dance community and how Sufi dance in the Dervishe Pekalongan community can increase the spiritual intelligence of its members. This research is field research (Field Research) with qualitative research methods. The approach used is religious phenomenology. The data collection techniques that researchers use are observation, interviews and documentation. The analysis used in this research is descriptive analysis. This study concluded that the spiritual intelligence of members of the Dervishe Pekalongan community increased before and after participating in Sufi dance. The indicators of spiritual intelligence that emerge are being adaptive, having empathy, tending towards kindness, having a high level of self-awareness, having patient qualities, having a big soul, helping and serving and being able to respond to problems well. This increase is due to the connection between indicators of spiritual intelligence and the meaning of a series of movements in performing Sufi dance. A series of movements in Sufi dance include crossing both hands on the shoulders, bowing, turning and prostrating.